Aircraft noise exposure and effects on the health of nearby residents: a review - Athirah, B.; Nurul Shahida, M. S. (Springer Science and Business Media Deutschland GmbH, 2021)
Noise exposure is a prevalent issue, where the people exposed to loud sources of sound. This paper presents a concise review on aircraft noise exposure and its effects on the health of people in nearby residences and public areas, par-ticularly on the health problems resulting from prolonged aircraft noise exposure and the noise levels that can cause disturbance to human hearing. For this review, 27 key works published from 2010 to 2020 was studied to find out the issues regarding the effect from aircraft noise exposure. Based on the growing number of published studies in this area, there is growing concern on noise pollution worldwide, with aircraft noise being one of the major types of noise pollution. Thus, the key findings were extracted from the published literature into the fol-lowing categories: (1) source of noise and propagation of noise, (2) recommen-dation of noise level from various boards, (3) effect and impact on nearby resi-dents, and (4) remedial actions to mitigate the effects of aircraft noise. This paper provides insight on aircraft noise, including ways to reduce the effects of aircraft noise based on the guidelines set by the authorities.